2007
DOI: 10.1093/nar/gkl828
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryotic genome size databases

Abstract: Three independent databases of eukaryotic genome size information have been launched or re-released in updated form since 2005: the Plant DNA C-values Database (), the Animal Genome Size Database () and the Fungal Genome Size Database (). In total, these databases provide freely accessible genome size data for >10 000 species of eukaryotes assembled from more than 50 years' worth of literature. Such data are of significant importance to the genomics and broader scientific community as fundamental features of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
409
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 445 publications
(425 citation statements)
references
References 22 publications
15
409
0
1
Order By: Relevance
“…1, Table 1). The small genome sizes of the cosmopolitan species C. fuscipes and P. cinerea seem to have evolved independently given that the two species are not closely related and that much larger genomes have been estimated for other psychodids, including C. albipunctata (this study), Telmatoscopus meridionalis (referenced in Gregory et al 2007), Phlebotomus papatasi and Lutzomyia longipalpis (J. S. J., unpublished data). Furthermore, the small genome sizes of C. fuscipes and P. cinerea cannot be explained by an unusually fast developmental rate.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…1, Table 1). The small genome sizes of the cosmopolitan species C. fuscipes and P. cinerea seem to have evolved independently given that the two species are not closely related and that much larger genomes have been estimated for other psychodids, including C. albipunctata (this study), Telmatoscopus meridionalis (referenced in Gregory et al 2007), Phlebotomus papatasi and Lutzomyia longipalpis (J. S. J., unpublished data). Furthermore, the small genome sizes of C. fuscipes and P. cinerea cannot be explained by an unusually fast developmental rate.…”
Section: Resultsmentioning
confidence: 83%
“…The smallest insect genomes reported so far belong to highly specialized parasitic species including the louse Pediculus humanus (1C=105 Mb; Johnston et al 2007) and the strepsipteran Caenocholax fenyesi texensis (1C=108 Mb; Johnston et al 2004). The next to follow in size are the genomes of certain dipteran midges (Mayetiola destructor, Cecidomyidae; Prodiamesa olivacea, Chironomidae) with 1C>120 Mb (Zacharias 1979;Petitpierre 1996;Johnston et al 2004), but genome size estimates of other dipterans are distinctly larger (1C> 140 Mb, Gregory et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a growing body of evidence indicates large variation in genome size in the fungal kingdom. While about 90 % of estimations range from 10 to 60 Mbp (Gregory et al 2007), extreme haploid genome sizes of up to 795 Mbp have been reported for Scutellospora castanea (Glomeromycota; Hosny et al 1998, Hijri andSanders 2005). The Ascomycota are well represented throughout this range, with estimates of 7.7 Mbp for Bulgaria inquinans (order Helotiales; Weber 1992) to 750 Mbp for Neottiella vivida (order Pezizales; Kullman 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Although the important role that fungi play in ecosystem diversity and functioning is under active research (e.g., Read and Perez-Moreno 2003), until recently, there has been relatively scarce information on genome structure and size for non-model fungal species despite its relevance for comparative biodiversity research (Gregory et al 2007). Nevertheless, a growing body of evidence indicates large variation in genome size in the fungal kingdom.…”
Section: Discussionmentioning
confidence: 99%
“…For the identification of heterozygosity in nonhaploid organisms or homologous loci of larger genomes (e.g., >100 Mbps), deeper sequencing depths will be necessary with additional modifications, such as adapters that include random degenerate sites for identifying PCR duplicates (Hoffberg et al., 2016), a narrower selection of read lengths, multiplexing fewer samples per library, or applying this protocol on the HiSeq. This study suggests that for haploid fungi that have relatively small genome sizes (30‐50 Mbps; Tavares et al., 2014; Gregory et al., 2007), increasing sequencing depths beyond 200k per sample will sufficiently decrease the error rates per locus and will be robust for fine‐scale genetic analyses.…”
Section: Discussionmentioning
confidence: 99%